Diet‐independent relevance of serum uric acid for blood pressure in a representative population sample. Issue 10 (29th June 2017) - Krupp, Danika; Esche, Jonas; Mensink, Gert BM; Neuhauser, Hannelore K; Remer, Thomas
Abstract : A direct relationship between serum uric acid and blood pressure (BP) has been reported, but the possible confounding impact of diet on this association is unclear. The authors performed a cross‐sectional analysis in the representative German Health Interview and Examination Survey for Adults (n=6788, aged 18–79 years). In adjusted regression models considering dietary factors, each 1‐mg/dL higher uric acid value was associated with a 1.10‐mm Hg ( P =.0002) and a 0.60‐mm Hg ( P =.04) higher systolic BP among participants younger than 50 years and participants 50 years and older, respectively. For diastolic BP, uric acid was a significant predictor (β=0.71 mm Hg, P =.0001) among participants younger than 50 years and for participants 50 years and older without antihypertensive treatment. Adjusted odds ratios of hypertension for participants with hyperuricemia were broadly similar in younger (odds ratio, 1.71; P =.02) and older (odds ratio, 1.81; P =.0003) participants. Uric acid is a significant predictor of systolic BP and hypertension prevalence in the general adult population in Germany independently of several known dietary BP influences.